2001
DOI: 10.1093/ei/39.4.511
|View full text |Cite
|
Sign up to set email alerts
|

Panel Tests of Okun's Law for Ten Industrial Countries

Abstract: Okun's Law is one of the most enduring stylistic facts in macroeconomics. This article uses new developments in trend/cycle decomposition to test Okun's Law for a panel of ten industrial countries, finding that Okun's original estimate for the U.S. of three points of real GDP growth for each one percent reduction in the unemployment rate now averages just under two points of real GDP growth for the sample countries. Pooled estimates for Europe are smaller than estimates for the rest of the sample. Also, this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 23 publications
3
55
0
3
Order By: Relevance
“…Since the relationship is indigenously bidirectional, researchers have been juggling the equations and have regressed both, output on unemployment (e.g. Freeman, 2001) and vice versa (e.g., Sögner and Stiassny, 2000). Yet, the interpretation of the results frequently misguided the authors and Okun himself, which leads to spurious results.…”
Section: And ( C I Y U I T =mentioning
confidence: 99%
“…Since the relationship is indigenously bidirectional, researchers have been juggling the equations and have regressed both, output on unemployment (e.g. Freeman, 2001) and vice versa (e.g., Sögner and Stiassny, 2000). Yet, the interpretation of the results frequently misguided the authors and Okun himself, which leads to spurious results.…”
Section: And ( C I Y U I T =mentioning
confidence: 99%
“…1962-1995, Freeman (2001 has found a value of about −0.25 for Japan, which is the lowest out of ten industrialized countries. Also, Moosa (1997) has reported that the value for Japan is the lowest one.…”
Section: Data Descriptionmentioning
confidence: 99%
“…Le résultat relatif à la variable indicatrice associée aux études régionales (REG) peut à priori apparaître incohérent avec le fait que les estimations régionales de la relation activité-chômage suggèrent généralement que cette relation est plus faible au niveau régional qu'au niveau national [par exemple : Freeman 2001;Christopoulos 2004ou Villaverde-Maza 2009. Cependant, toutes les études régionales retenues dans la présente méta-ré-gression sont basées sur des équations d'Okun dans lesquelles le PIB réel apparaît comme la variable expliquée.…”
Section: Analyse De Type Metaregression Multivarieeunclassified